1991
DOI: 10.1093/brain/114.3.1281
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Muscle Nerve Activity During Sleep in Man

Abstract: Muscle sympathetic activity (MSA) was recorded in the peroneal nerve during sleep in 14 sleep-deprived healthy subjects. Continuous noninvasive recordings of finger blood pressure were obtained in 7 subjects. In light sleep (stage 2 sleep) the number of sympathetic bursts/min decreased to 90 +/- 8% (mean +/- SEM) and total MSA (= burst/min x mean burst area) to 89 +/- 5% of the awake value (P less than 0.05, n = 14). In deep sleep (stage 3-4) total MSA decreased further, to 71 +/- 8% of the awake value (n = 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
140
0
7

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(161 citation statements)
references
References 0 publications
14
140
0
7
Order By: Relevance
“…This overall picture points to a cardiac parasympathetic predominance during non-REM and to a peripheral sympathetic activation during REM, in agreement with studies that directly recorded peripheral sympathetic nerve traffic. [5][6][7] The lack of a tachycardic effect, despite the simultaneous increase sympathetic activation, frequently reported during REM 5,6,24,25 could be explained through a vagally mediated baroreflex mechanism offsetting cardiac sympathetic activation, as suggested by the increase in BRS in response to hypertensive stimuli. 25 As to the lack of significant changes in BRS downsequences, a different buffering effect of arterial baroreflex in response to increases and decreases in BP during sleep has Symbols indicate between-condition differences as follows: *Awake vs non-CAP; †Awake vs CAP; ‡Awake vs REM; §CAP vs non-CAP; ¶CAP vs REM; ʈNon-CAP vs REM; **Not significant vs non-CAP S2; † †Not significant vs non-CAP S2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This overall picture points to a cardiac parasympathetic predominance during non-REM and to a peripheral sympathetic activation during REM, in agreement with studies that directly recorded peripheral sympathetic nerve traffic. [5][6][7] The lack of a tachycardic effect, despite the simultaneous increase sympathetic activation, frequently reported during REM 5,6,24,25 could be explained through a vagally mediated baroreflex mechanism offsetting cardiac sympathetic activation, as suggested by the increase in BRS in response to hypertensive stimuli. 25 As to the lack of significant changes in BRS downsequences, a different buffering effect of arterial baroreflex in response to increases and decreases in BP during sleep has Symbols indicate between-condition differences as follows: *Awake vs non-CAP; †Awake vs CAP; ‡Awake vs REM; §CAP vs non-CAP; ¶CAP vs REM; ʈNon-CAP vs REM; **Not significant vs non-CAP S2; † †Not significant vs non-CAP S2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies dealing with sleep-related neural cardiovascular regulation [5][6][7][23][24][25] have focused on the conventional scoring defining the sleep macrostructure. 13 As in these studies, we observed a decrease in BP during S2 and SWS, with a recovery to the awake level during REM associated with parallel changes in LF SBP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 18 Cardiac metabolic gene expression anticipates and aligns with this circadian variation in myocardial workload. 19 Synchrony of these metabolic, temporal and autonomic rhythms, fundamental to normal cardiovascular homeostasis, 20 is disrupted profoundly by SDB.…”
Section: Acute Eventsmentioning
confidence: 99%
“…The difference in thresholds and the response to analgesics in both legs before and after injury to the left suggests that there are both central and peripheral aspects to the increase in pain sensitivity. (Parmeggiani & Morrison, 1990) and in humans (Hornyak et al 1991), and it has been speculated that cardiac parasympathetic activity would increase during non-REM sleep. Using the absolute differences in consecutive R-R intervals in a continuous ECG (beat variability, BV) (Julu & Hondo, 1992), we have measured the BV during progressive stages (1-3) of non-REM sleep in 5 sleepdeprived subjects (10-53 years old).…”
Section: Referencesmentioning
confidence: 99%